Meningkatkan Kemampuan Membaca Melalui Media Gambar pada Anak Usia Dini di Kelas B RA Bahrul Ulum NW Telaga Bagik: Improving Reading Skills Through Picture Media in Early Childhood in Class B RA Bahrul Ulum NW Telaga Bagik - Ittihad (Al-Gafari : Manajemen dan Pendidikan, 2025)
Early childhood is a group of children who are in a unique growth and development process. They have a specific growth and development pattern according to their growth and development level. This study aims to determine whether image media can improve the reading skills of early childhood in class B RA Bahrul Ulum NW Telaga Bagik. This study is a participatory Classroom Action (CAR) with the Kurt Lewin model design. The number of cycles used in the study was two cycles. Each cycle used two meetings. The subjects of the study were children in class B RA Bahrul Ulum NW Telaga Bagik consisting of 7 male students and 8 female students with a total of 15 students. Data were collected using an instrument in the form of an observation sheet with an assessment scale. The credibility test in this study used the participation extension examination technique. The data analyzed were the difference in value between cycle I and cycle II using a one-sample t-test with one-party testing criteria: namely the right side. The calculation results showed , namely 9.667> 1.761, these results indicate that Ha is accepted. In conclusion, image media can improve the reading skills of early childhood in class B RA Bahrul Ulum NW Telaga Bagik.